Leadership Style, Supervision Techniques, Competencies, and Implementation of Professional Nursing Practices on Service Quality: A Cross-Sectional - Wahyuni, Marisca Astri; Pamungkas, Rian Adi; Mustikawati, Intan Silviana (Alta Dharma Publisher, 2024)
Background: The provision of high-quality healthcare services is a critical. Objective: This study aims to investigate the influence of leadership style, supervision techniques, and competence on the quality of service at the Columbia Asia Pulomas Special Surgical Hospital with the implementation of professional nursing practice as an intervening variable. Method: The quantitative with an cross-sectional approach was used to determine the causality among variables. Data was collected from 105 nurses using purposive sampling techniques and analyzed using Structural Equation Modeling (SEM). Result: The result found that leadership style (p-value<.05), competencies (p-value<.05), and professional nursing practice (p-value<.05) have positive effect on quality of services. Professional nursing practice mediates the influence of the three independent variables on service quality. Conclusion: These findings show the importance of implementing the professional nursing practice model in improving the quality of nursing services. The democratic leadership style applied motivates nurses to provide quality services, while more effective supervision needs to be improved to ensure optimal service. Nurse competency plays a crucial role in producing quality services through professional nursing practice. Implication: This research contributes to the understanding of the factors that influence the quality of nursing services in hospitals and provides valuable input in improving service standards. Therefore, hospital leaders and management need to pay attention to the implementation of professional nursing practices as a strategy to improve the quality of nursing services